La trayectoria de los estudiantes de cuota racial en el Instituto Federal de Educación, Ciencia y Tecnologia do Rio Grande do Norte (2014-2023) - Leite de Lima, Izabel Cristina (2025)
This study analyzes the trajectories of students admitted through racial quotas at the Federal Institute of Education, Science, and Technology of Rio Grande do Norte (IFRN) between 2014 and 2023. The analysis focuses on per capita income, Grade Point Average (IRA), and dropout rates, comparing them with students admitted through broad competition over the same period. A mixed-methods approach was adopted, combining qualitative and quantitative analyses. Statistical data on income, IRA, and dropout rates were examined using descriptive methods, including mean and standard deviation comparisons between categories. The results show that quota students, particularly those from Black populations, have the lowest per capita incomes. It was found that, despite the similarity in academic performance between non-quota students and racial quota students, non-quota students have a higher IRA and a higher dropout rate.